Adaptation model of anglicisms - Zolotareva E. A. (Scientific studies from theory to practice, 2016)
the article addresses the issue of the classification of English loans in accordance with certain criteria. The authors emphasize the importance of multidimensional modeling of anglicisms, and it helps to see the borrowing in a structured way, contributing to a more specific and accurate definition of the phenomenon under study
Keywords: моделирование; modeling; англицизм; классификация заимствований; адаптационная модель; освоенные англицизмы; окказионализмы; трансплантант; transplant; anglicism; classification of loans; adaptation model; assimilated anglicisms; occasionalisms